Fisher's Paradox and the Theory of Interest - Carmichael, Jeffrey; Stebbing, Peter W. (American Economic Review, 2016)
Irving Fisher's Theory of Interest has proved to be a most durable and influential contribution to economic theory. A central element of Fisher's contribution is the Fisher hypothesis that, over the longer term, the real rate of interest is approximately constant, being determined largely by time preference, with movements in the nominal interest rate reflecting movements in the rate of inflation one-for-one. The paradox of the Fisher hypothesis is that, despite its wide acceptance as the cornerstone of interest rate theory, most empirical evidence appears to be inconsistent with the hypothesis, at least in its strictest form. This empirical anomaly was noted by Fisher himself, who attributed it to money illusion. In the fifty years following the publication of the Theory of Interest, a considerable literature has evolved around this paradox.' The unifying theme of this literature is a common acceptance of the essence of Fisher's hypothesis. Most of the energy in this literature has been devoted to explaining systematic movements in the real rate of interest, and to providing reasons why the relationship between the nominal interest rate and inflation may only be approximate in